Game-Based Learning, Gamification in Education and Serious Games - Vaz de Carvalho, Carlos (2022)
Video games have become one of the predominant forms of entertainment in our society, but they have also impacted many other of its social and cultural aspects. The new forms of interaction and communication in online multiplayer games, the millions of viewers of professional e-sports competitions, the huge following of gaming streamers through channels such as Twitch, and the communities of players that are formed around a specific title are just some examples of the impact of games in everyday life today.[...]